Generative AI in Arabic Grammar Learning: A Critical Review of Pedagogical Benefits and Linguistic Limitations - Muhammad Fariq Heemal Attruk; Nik Hanan Mustapha (MAN 4 Kota Pekanbaru, 2026)
The rapid development of generative artificial intelligence (AI) has significantly influenced Arabic language education, particularly in the learning of nahwu (syntax) and shorof (morphology). This study aims to critically examine the pedagogical benefits and linguistic limitations of generative AI in Arabic grammar learning through a narrative literature review approach. The study analyzes recent scholarly works on AI-assisted Arabic language instruction and grammatical analysis. The findings reveal that generative AI supports independent learning, provides immediate feedback, and increases learner engagement. However, persistent limitations remain in handling complex syntactic structures, contextual ambiguity, and accurate grammatical interpretation. The review also highlights concerns regarding learners’ overreliance on AI and the continuing need for teacher supervision. The study concludes that generative AI should function as a supportive instructional tool rather than a fully autonomous learning authority in Arabic grammar education.